Live birth after single embryo transfer of autologous cryopreserved oocytes from a patient with myelodysplastic syndrome who underwent allogenic peripheral blood stem cell transplantation - Yi-Yi Tsai; Shee-Uan Chen; Chia-Jen Shieh; Yi-Lin Yao; Yu-Shih Yang; Chin-Der Chen (Journal of the Formosan Medical Association, 2014)
We report a live birth after single embryo transfer derived from autologous cryopreserved oocytes of a patient with myelodysplastic syndrome who had undergone allogenic peripheral blood stem cell transplantation (PBSCT). In 2006, a 24-year-old female diagnosed with myelodysplastic syndrome was referred for fertility preservation before she underwent PBSCT. After controlled ovarian stimulation, 38 oocytes were retrieved for cryopreservation using a slow-freezing protocol. She was cured by PBSCT and entered menopause. After seven years, she requested thawing of the oocytes. She was prepared for a thawing cycle using hormone replacement therapy. Twenty-two cryopreserved oocytes were thawed, and 20 (91%) oocytes survived. Thirteen mature oocytes were inseminated by intracytoplasmic sperm injection. Ten (77%) oocytes were normally fertilized and 6 (60%) oocytes developed into blastocysts. Embryo transfer to her own uterus with one blastocyst was performed. Five blastocysts were vitrified. A sonographic exam at 7 weeks of gestation revealed one gestational sac with positive cardiac motion. A normal female baby weighing 2704 g was delivered at 40 weeks of gestation. A successful pregnancy from autologous cryopreserved oocytes is encouraging for cancer patients undergoing fertility preservation. For infertile cancer patients after PBSCT, we suggest the transfer of one embryo to reduce the risk of multiple pregnancies.